Forbidden knowledge from Prometheus to pornography - Shattuck, Roger 1923-2005 (St. Martin's Press, 1996)
Forbidden Knowledge boldly traces the tragic arc of Western literature and culture as it explores the notion of "forbidden knowledge," from the sexual innocence of Adam and Eve to the awe-inspiring discoveries of modern scientists who have created the atomic bomb and recombinant DNA. The result is a dire portrait of human presumption and of a culture that has abandoned all limits in the quest for knowledge and experience. The harrowing imagery that Shattuck presents is matched only by his faith that we can understand our grievous loss of innocence by reexamining our greatest myths and stories of the last two thousand years. In lively, lucid prose Shattuck explores our uncertain fate through such myths as that of Prometheus and a wide range of literary works, including Milton's Paradise Lost, the writings of the Marquis de Sade, Mary Shelley's Frankenstein, Melville's Billy Budd, and the poetry of Emily Dickinson. Parents and teachers should be aware that Chapter VII does not make appropriate reading for children and minors. In this seminal work, Shattuck breaks new ground in opening up a crucial subject never before accorded this full-scale treatment. Forbidden Knowledge impels us to a renewed effort to think judiciously about morality and the sacred during a decade of radical skepticism. Forbidden Knowledge represents the capstone of Roger Shattuck's career as one of America's most original and gifted thinkers.